EVALUATION OF OXIDATIVE METABOLIC DISORDERS IN WOMEN SUFFERING FROM CHRONIC INFLAMMATORY DISEASES OF SMALL PELVIS - I. A. Egorova; V. A. Krutova; A. G. Zavgorodnyaya (Кубанский научный медицинский вестник, 2018)
Aim. The study was conducted to evaluate the intensity of oxidative disorders in women suffering from a complex course of chronic endometritis and salpingo-oophoritis. Materials and methods. The study was performed on 85 women divided into 3 groups: the control group – relatively healthy patients (n=30), the 2nd group – the patients suffering from chronic endometritis (n=29), the 3rd group – the patients suffering from a complex course of chronic endometritis and bilateral salpingo-oophoritis (n=26). The indices of chemiluminescence induced by the hydrogen peroxide were determined in the blood plasma and the mixed oral liquid. The content of products of oxidative modifications reacting to the thiobarbituric acid was determined in the erythrocyte meal and the mixed oral liquid.Results. The evaluation of the content of the product of oxidative modifications in biomolecules as well as the level of luminal-dependent chemiluminescence induced by the hydrogen peroxide revealed the intensification of free-radical processes in blood and the mixed oral liquid of patients suffering from inflammatory diseases of small pelvis. The index of the thiobarbituric value and the maximal chemiluminescence flash increased by 60-70% in the blood of patients from the 2nd-3rd groups. The area of chemiluminescence flash of the blood plasma in patients suffering from chronic endometritis increased by 73%, while in patients suffering from a complex course of chronic endometritis and bilateral salpingo-oophoritis it was significantly higher – by 2.1 times. The increase in the value of the maximal chemiluminescence flash by 45% and the chemiluminescence area by 43% was detected in the mixed oral liquid of the patients from the 3rd group, while the increased value of only chemiluminescence area (by 42%) was revealed in patients of the 2nd group.Conclusion. The results of the performed study revealed that the intensity of oxidative processes on the local and systemic levels in patients suffering from a complex course of chronic endometritis and double salpingo-oophoritis was significantly higher than in patients suffering from an isolated course of endometritis.